Field study 5 : learning assessment strategies - Lucido, Paz I. (Cubao, Philippines : Lorimar Publishing Company Inc., 2010)
FS5 Workbook aligns the learner's experiences with the National Competency-Based Teacher Standards (NCBTS). The learning experiences en=mbedded in every lesson were intended to create meaningful and rewarding encounters that the students will feel the joy of teaching and learning. FS5 includes "Guiding Principles in the Assessment of Learning", "Using Appropriate Assessment Tools", "On Content Validity of Tests", " On Scoring Rubrics"," On Portfolios", and "Scoring, Grading and Communicating Results.
Foreword ii -- Preface iv -- Letter to the Field Study Student vii -- Letter to Field Study Teacher viii -- Orientation Notes for Field Study and this Workbook ix -- Suggested Guidelines for Field Study Student xiv -- Field Study 5 - Learning Assessment Strategies 1 -- FS 2 - Guiding Principles in the Assessment of Learning 2 -- FS 2 - Using Appropriate Assessment Tools 8 -- FS 2 On Content Validity of Tests 15 -- FS 2 - On Scoring Rubrics 24 -- On Portfolios 32 -- Scoring, Grading and Communication Results 39 -- Certificate of Completion of Experiential Learning Courses Prescribed by DepEd
Corpuz, Brenda B.
Keywords: EDUCATIONAL EVALUATION